EVALUATION OF INTERACTIVE PHYSICAL ACTIVITY EDUCATION PROGRAM (IPAEP): A PRELIMINARY STUDY - Ahmad Faezi Ab. Rashid; Nor Dalila Marican; Abdullah Mohamed Yusoff; Nurul Hafizah Mohd Yasin; Mohd Hafzal Abdul Halim; Hasif Rafidee Hasbollah, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The purpose of this study was to evaluate changes in physical activity knowledge among university students after exposure to Interactive Physical Activity Education Program (IPAEP). In current globalization, physical inactivity or sedentary lifestyle becomes a major underlying cause of chronic diseases worldwide. There is a growing concern of inadequate physical activity levels among young adult especially university students. The acquisition and dissemination of physical activity recommendations through physical activity program are essential in the delivery of an adequate level of physical activity knowledge among university students Materials and Methods: A quasi-experimental study design was conducted, and data were collected using a questionnaire among students (n=116) of Universiti Malaysia Kelantan, to evaluate the changes of physical activity knowledge after exposure to IPAEP intervention. All of them participated in 10 weeks of IPAEP intervention. In the IPAEP intervention, students were exposed to interactive lecture and various online activities related to types, risks, benefits, and key recommendations of physical activity. Pre- and post-intervention survey were taking place before and after the program to evaluate the same measure, which is the physical activity knowledge. Data were analyzed using IBM SPSS version 25.0. Paired-sample t-tests were used to evaluate the differences between pre- and post-intervention of the physical activity knowledge scores. Result: The present study showed significant increment in physical activity knowledge score (P-value <0.001) among university students after participating in IPAEP intervention. Conclusion: Since the present study emphasized physical activity education for university students, the IPAEP could contribute to the better physical activity knowledge which eventually beneficial for their active lifestyle in the future.